Root and tuber crops in Guadeloupe - Degras, L. (International Center for Tropical Agriculture, 1986)
The main root crops grown in Guadeloupe and their annual production rates are indicated. Very few areas of the island are planted to cassava; this root crop is grown in mixed cropping systems (aroids/cassava/cocoa/coffee, aroids/sweet potato/cassava, or cassava/sweet potato) or in monoculture in the north of Grande- Terre, in Marie-Galante, and over the Capesterre-Belle-Eau area of Basse-Terre. Both sweet and bitter cv. are grown. Since the 2nd World War, root crop production in Guadeloupe, especially that of cassava, has declined due to the importation of other carbohydrate commodities, diversification, rise in prices for export crops, lack of growers' associations, and adoption of European and North American consumption patterns. (CIAT)